PENGARUH FAKTOR-FAKTOR KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN MITRA PEMBAYARAN ONLINE DI PT ARINDO PRATAMA BANDUNG - Nurdiansyah, Haris; Rahman, Robbi Saepul (Majalah Bisnis & IPTEK, 2021)
This study aimed to identify and assess the Influence Factors of Service Quality Customer Satisfaction Partner Online Payment Arindo PT Pratama Bandung. The method used in this research is the analysis of the path, because this research in addition to want to get an overview of customer satisfaction associated with Tangible, reliability, responsiveness, assurance and empathy, also wanted to get a picture of the pattern of the relationship and the influence of the variables research has been established. Based on the results of the study, found that tangible in PT. Arindo Pratama Bandung are in good enough category. Then reliability, Responsiveness, Assurance and Empathy in good enough category. In general, Tangible, Reliability, Responsiveness, Assurance and Empathy effect on Customer Satisfaction Partner Online Payment in PT Arindo Pratama Bandung. The effect of partially variable Tangible against Customer Satisfaction is 0.169 or 16.9%, variable reliability of the Customer Satisfaction is equal to 0.127 or 12.7%, variable Responsiveness to Customer Satisfaction is equal to 0.306 or 30.6%, variable against Satisfaction Guarantee Customers amounted to 0.054 or 5.4% and variable Empathy towards customer satisfaction is equal to 0.222 or 22.2%. Simultaneous influence of Tangible, reliability, Responsiveness, Assurance and Empathy towards Customer Satisfaction amounted to 0,879, or 87.9%, whereas 0.121 or 12.1% is influenced by other variables not examined in this study. From the research that is done, then the variable Tangible, Reliability, Responsiveness, Assurance and Empathy when combined will have a significant impact on Customer Satisfaction Partner Online Payment in PT Arindo Pratama Bandung. Keywords: tangible; reliability; responsiveness; empathy; customer satisfaction.